2021
DOI: 10.3389/fcell.2021.681238
|View full text |Cite
|
Sign up to set email alerts
|

The Latest Research Progress of m6A Modification and Its Writers, Erasers, Readers in Infertility: A Review

Abstract: Eukaryotic messenger mRNAs contain many RNA methyl chemical modifications, in which N6-methyladenosine (m6A) plays a very important role. The modification process of RNA methylation is a dynamic reversible regulatory process that is mainly catalyzed by “Writer” m6A methyltransferase, removed by “Eraser” m6A demethylase, and recognized by the m6A binding protein, thereby, linking m6A modification with other mRNA pathways. At various stages of the life cycle, m6A modification plays an extremely important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 137 publications
1
7
0
Order By: Relevance
“…YTHDC2 is highly expressed in the testes and has been linked to spermatogenesis in recent studies. [19][20][21][22][23]48,[66][67][68][69][70][71] YTHDC2 was highly expressed in pachytene spermatocytes (Figure 1A), which was consistent with the experimental validation. [48] Several studies have found that YTHDC2 regulates meiosis via different signaling pathways.…”
Section: A Modification-controlled Spermatocytes Developmentsupporting
confidence: 85%
See 3 more Smart Citations
“…YTHDC2 is highly expressed in the testes and has been linked to spermatogenesis in recent studies. [19][20][21][22][23]48,[66][67][68][69][70][71] YTHDC2 was highly expressed in pachytene spermatocytes (Figure 1A), which was consistent with the experimental validation. [48] Several studies have found that YTHDC2 regulates meiosis via different signaling pathways.…”
Section: A Modification-controlled Spermatocytes Developmentsupporting
confidence: 85%
“…[49] Recent studies have shown that YTHDF2 is required for the development of spermatogonia. [20][21][22][23] The inhibition of the G2 phase in GC-1 cells was caused by Ythdf2 depletion. Furthermore, YTHDF2 modulated cell-matrix adhesion mainly by regulating matrix metallopeptidase (MMPs) and extracellular matrix (ECMs) expression, and matrix metallopeptidase 13 (Mmp13) is an important target for YTHDF2 to regulate the phenotype.…”
Section: A Modification Regulated Spermatogonia Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Precise treatment of m6A-related gene targets, including but not limited to METTL3, METTL14, WTAP, KIAA1429, FTO, YTHDC1, YTHDC2, and YTHDF2, by regulating RNA m6A modifications, can potentially ensure normal gametogenesis, which has a therapeutic effect on infertility. Since miR-186, miR-4429, miR-600, and STM2457 have been shown to target METTL3 mRNA and inhibit its expression (Zeng et al 2020, Yankova et al 2021, Wu et al 2022), these three micro-RNAs and STM2457 can be used in the treatment of gametogenesis disorders (Liu et al 2021). FTO inhibitors are used in patients with FTO gene abnormalities.…”
Section: Perspectivesmentioning
confidence: 99%